China-U.S. Oil Rivalry in Africa - Zhao Hong (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2007)
China is now the world's second largest oil-consuming country after the U.S.. Its global efforts to secure oil imports to meet increasing domestic demand have profound implications for international relations in the Asia-Pacific region. China's rising oil demand and its external quest for oil have thus generated much attention. As China's overseas oil quest intensifies, will China clash with the U.S. and other western countries' interests in Africa, and how does it look at this rivalry? Will China disrupt the U.S. and its allies' foreign policy and the world order? China, oil strategy, African oil, U.S., energy rivalry
hdl:10398/7411
Keywords: 330